2018
DOI: 10.1016/j.otsr.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Management of the floating shoulder: Does the glenopolar angle influence outcomes? A systematic review

Abstract: Therapeutic level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…The glenoid covers only one third of the humeral head articular surface and the joint capsule is relatively lax. This makes the joint highly susceptible to instability and prone to dislocation [28] . Glenohumeral dislocation account for 50% of all dislocations and are most common in young men [3] .…”
Section: Glenohumeral Dislocationmentioning
confidence: 99%
“…The glenoid covers only one third of the humeral head articular surface and the joint capsule is relatively lax. This makes the joint highly susceptible to instability and prone to dislocation [28] . Glenohumeral dislocation account for 50% of all dislocations and are most common in young men [3] .…”
Section: Glenohumeral Dislocationmentioning
confidence: 99%
“…More recently the glenopolar angle has been added to the list and shows promise, though a recent systematic review demonstrated that the positive relationship between glenopolar angle and outcome that has been published will need larger studies to prove. 28 It is not unusual to hear medialization of the glenoid mentioned as an indication for surgery, but care should be taken with this concept. Apparent medialization is actually often caused by lateral displacement of the lateral border of the scapula under the influence of the attached teres muscles.…”
Section: Indications For Surgerymentioning
confidence: 99%
“…In einer 2018 veröffentlichten Metaanalyse von Morey et al wurden die verschiedenen Behandlungsoptionen (konservative Therapie, die isolierte Versorgung der Klavikulafraktur oder die kombinierte Adressierung von Skapulahals und Klavikula) verglichen. Keine Strategie zeigte sich der anderen überlegen, die Rekonstruktion des glenopolaren Winkels ist auch hier Grundvoraussetzung für ein gutes Ergebnis [39].…”
Section: Versorgung Einer Sssc-verletzungunclassified